Evaluation of Optimal Pore Size of (3-Aminopropyl)triethoxysilane Grafted MCM-41 for Improved CO2 Adsorption - Zhilin Liu; Yang Teng; Kai Zhang (Journal of Chemistry)
An array of new MCM-41 with substantially larger average pore diameters was synthesized through adding 1,3,5-trimethylbenzene (TMB) as the swelling agent to explore the effect of pore size on final adsorbent properties. The pore expanded MCM-41 was also grafted with (3-Aminopropyl)triethoxysilane (APTES) to determine the optimal pore size for CO2 adsorption. The pore-expanded mesoporous MCM-41s showed relatively less structural regularity but significant increments of pore diameter (4.64 to 7.50 nm); the fraction of mesopore volume also illustrated an increase. The adsorption heat values were correlated with the order of the adsorption capacities for pore expanded MCM-41s. After amine functionalization, the adsorption capacities and heat values showed a significant increase. APTES-grafted pore-expanded MCM-41s depicted a high potential for CO2 capture regardless of the major drawback of the high energy required for regeneration.